A Teachers’ Journey: Phenomenological Analysis in Teaching Research - Reynaldo V. Moral (Researchparks Publishing, 2022)
This study portrays the lived experiences of some research teachers from different public and private schools in Cebu City who taught specific research subjects in the senior high schools for the first semester of 2018-2019. The main goal of this study is to explore the educational practices of the nine teacher respondents based on their trials, adjustments, managing mechanisms, who showed willingness to participate. The descriptive phenomenological design was used by the researcher from Husserlian philosophy using Colaizzi Data Analysis. Semi-structured interviews were collated and coded after bracketing. Furthermore, the field notes were used for the informants upon asking their consent as a form ethical consideration. The highlights of the experiences of these research teachers are condensed in the following themes: “Different Strokes for Different Strokes”; “Invest and Harvest”; “Art of Communication”; “Between Hard and Soft”; Time will Reveal”; and “Technology Conquers Limitations.” Results also showed that the research teachers still consider the whole experience worthwhile and beneficial despite “scanty of instructional materials and relevant trainings” which has long been a predicament in enriching the curriculum.